Inclusive Learning in Elementary Schools Against Islamic Religious Education Lessons - Kristo Paulus; Raihan Raihan; Sutarjo Sutarjo (Ilomata International Journal of Social Science, 2022)
Learning Inclusive Islamic Religious Education in Elementary Schools still needs to be improved. religious learning must be carried out even if the child seems slow to learn (slow learner) in following Islamic religious lessons, taking into account the following matters: prepare teaching materials and materials to meet the unique and specific needs of students, the most effective learning methods to use in the delivery of learning materials or materials, provide continuous attention and motivation. Focus on paying attention so that students know that the teacher who teaches pays attention to them when in class, it is important to make eye contact when learning takes place, give appreciation and appreciation for their presence. parental support, encouragement and seriousness are closely related to slow children's learning outcomes. In qualitative research, the instrument or research tool is the researcher himself. The approach used in this study is to use a phenomenological approach. This study aims to examine the learning conditions of Inclusive Islamic Religious Education in Public Elementary Schools, as well as to analyze, evaluate and the learning model of Inclusive Islamic Religious Education in public elementary schools.